Proses Produksi Industri Pandai Besi di Kecamatan Togo Binongko Kabupaten Wakatobi - Leni, Leni; Mardin, Mardin; Suriana, Suriana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study aimed to determine the production process of the blacksmith industry in Togo Binongko District, Wakatobi Regency, in May 2019. The determination of the research location was determined purposively. Respondents in this study were heads of families who worked as blacksmiths in Togo Binongko District, Wakatobi Regency, with as many as 20 respondents. Data analysis uses quantitative data analysis techniques to describe the data that has been collected and present the data in tabular form so that it becomes clearer according to the conditions in the field. The results showed that the agricultural equipment produced by the smart in Togo Binongko District was made through a traditional production process while maintaining product quality. The production process starts from Tila and Tihi (sorting and cutting of iron raw materials), Kepa'a (forging), Hokomonde'a (modeling), and Soropu'a (re-burning). Blacksmith artisans can maintain the quality of the products produced by improving the production process by participating in training and using equipment that can increase production efficiency.